Depression and diabetes distress in patients with diabetes. Issue 1 (February 2023) - Boehmer, Kaci; Lakkad, Mrinmayee; Johnson, Chris; Painter, Jacob T.
Abstract: We aimed to identify the prevalence of comorbid depression, diabetes, and diabetes distress and assess glycemic control and rates of diabetes-related complications. While the presence of either depression or distress did not predict the level of glycemic control, certain macro- and microvascular complications were more prevalent with depression. Highlights: Depression and diabetes distress (DD) have been linked to worse glycemic control.. Prevalence of depression and DD can be difficult to estimate. There is limited data on whether they are associated with diabetes complications. In this study, neither depression nor DD correlated with glycemic control. Those with depression were more likely to have diabetes-related complications.